Endoplasmic reticulum stress signaling modulates ischemia/reperfusion injury in the aged heart by regulating mitochondrial maintenance - Ji Zhang; Yuanyuan Zhao; Nianqiao Gong (BMC, 2024)
Abstract Aging is associated with an increased risk of myocardial ischemia/reperfusion injury (IRI). With an increasing prevalence of cardiovascular diseases such as coronary arteriosclerosis in older people, there has been increasing interest in understanding the mechanisms of myocardial IRI to develop therapeutics that can attenuate its damaging effects. Previous studies identified that abnormal mitochondria, involved in cellar senescence and oxidative stress, are the master subcellular organelle that induces IRI. In addition, endoplasmic reticulum (ER) stress is also associated with IRI. Cellular adaptation to ER stress is achieved by the activation of ER molecular chaperones and folding enzymes, which provide an important link between ER stress and oxidative stress gene programs. In this review, we outline how these ER stress-related molecules affect myocardial IRI via the crosstalk of ER stress and mitochondrial homeostasis and discuss how these may offer promising novel therapeutic targets and strategies against age-related cardiovascular diseases.